Pengaruh Citra Sekolah dan Kualitas Pelayanan terhadap Kepuasan Wali Murid pada TK An-Nabil Bumi Jati Elok Kabupaten Tangerang - Widiastuti, Cantya; Ardianto, Ardianto; Faroh, Wahyu Nurul (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the effect of school image and service quality on parent satisfaction at An-Nabil Bumi Jati Elok Kindergarten in Tangerang Regency. This study uses a quantitative causal method with a saturated sampling technique and a total of 73 respondents. The results show that school image has a positive and significant effect on parent satisfaction with a coefficient of determination of 53.2%. The partial hypothesis test shows that tcount > ttable (8.989 > 1.993) and Sig (<0.001 < 0.05), thus Ho is rejected and Ha is accepted. Service Quality has a positive and significant effect on Parent Satisfaction with a coefficient of determination of 64.8%. The partial hypothesis test obtained tcount > ttable (11.437 > 1.993) and Sig (<0.001 < 0.05), thus Ho is rejected and Ha is accepted. School Image and Service Quality have a positive and significant effect on Parent Satisfaction, with a simultaneous coefficient of determination of 69.6%. The simultaneous hypothesis test was influenced by the Fcount > Ftable (79.957 > 3.128) and sig (< 0.001 < 0.05) values, thus Ho was rejected and Ha was accepted. This means that school image and service quality have a positive and significant simultaneous effect on parent satisfaction.